(Dis)Continuities in Racialized Legal Violence. (March 2021) - Ward, Geoff; Cunningham, David; Lee, Hedwig; Gaby, Sarah
Amid growing research on the history and legacies of racist violence in the United States, there has been limited development of theory and measurement pertaining to racist violence as a sociological process. Social science research has centered on lynching and, to a lesser extent, slavery and broader Jim Crow laws and customs, and rarely have these and other forms been engaged together and in relation to contemporary outcomes. We focus on racialized "legal violence"—uses of law in ways that are harmful to populations defined by race—and use the case of South Carolina "slave courts" to explore modes of racialized violence that are expansive and intertwined. Contrary to a more sequential and linear reading of successive and discreet modes of repression (e.g., "slavery ended. . ."), our analysis shows recursive, multidimensional, and cascading aspects of injurious legal action and inaction that accumulate and repeat over time. Continuities of racialized legal violence, which are contested and thus dynamic, modify and maintain age-old structural constraints. Rather than unfolding in sequence—from settler colonialism to enslavement, Jim Crow, and mass incarceration—"peculiar institutions" are more fluid, sharing repertoires and networks of racialized legal violence that recombine over time.